Ambiente de prática e empoderamento de enfermeiros de um hospital universitário - Moura, Lenize Nunes (2019)
Empowerment derives from work environment composed of several characteristics that, when evaluated as positive by the workers, result in better professional performance, especially in hospital settings. Therefore, the presence of certain characteristics in the professional practice environment can contribute to obtain better results, especially with regard to nursing care. The present study had as objective analysing the characteristics of the professional practice environment and measuring the levels of structural nurses’ empowerment of a university hospital of Brazil southern. This is a cross-sectional, descriptive study with a quantitative methodological approach. The research was carried out in a university hospital in Brazil southern, from February to June 2018. The research sample consisted of 237 nurses who worked in different units, such as Hospitalization Units; Surgical and obstetric area, Intensive Care Units; Hemato-oncology; Emergency Room; Psychiatry and Ambulatory. The data collection was done through the application of three self-responding instruments: personal, professional and work environment characterization form; and, the Brazilian version of the Nursing Work Index – Revised (NWI-R) and Conditions of Work Effectiveness II (CWEQ-II). Data analysis was performed in the Statistical Package for Social Sciences (SPSS) version 21. All ethical principles regarding human research were respected, in accordance with Resolution 466/2012. The study was attended by 237 (86.1%) nurses, most of them female (88.2%), with an average age of 38 years. The results showed that the environment is favorable to the nurses’ professional practice. The means of NWI-R subscales were: "autonomy" (2.26), "control over the environment" (2.39), "relationships between doctors and nurses" (2.29) and "organizational support"(2.27). These values indicate that nurses have autonomy, control over the environment, good relationships with doctors and nurses, and organizational support. Regarding the CWEQ-II results, a mean of 18.06 was identified, revealing that the nurses participating in the study have a moderate level of structural Empowerment. The greatest value was obtained in the Opportunity dimension (4.08), followed by the Resources (3.17) and Informal Power dimension (3.04); while the scores for Support (2.67), Formal Power (2.59) and Information (2.51) were the lowest. It can be concluded that the practice environment was evaluated as favorable to professional practice, nurses have autonomy, control over the environment, good relations with doctors and nurses, and organizational support. Nurses have a moderate level of structural Empowerment in the work environment, when they perceive a greater access to opportunity, followed by resources, support and information, allowing the development and professional performance within the work environment. Therefore, it is important to emphasize the importance of managers investing in the construction of favorable environments, in which nurses feel empowered, in a way that leads to greater professional satisfaction and improvement the care quality, bringing improvements to hospital organizations.